Amino acids composition and antioxidant activity of selected mushrooms from Bosnia and Herzegovina - Salihović, Mirsada (Array, 2019)
Many studies highlight the health benefits of mushrooms, which are consequently becoming more and more interesting for researchers. The content of amino acids (AA), total phenolic content (TPC), and antioxidative activity (AAc) were determined in wild as well as cultivated mushrooms. The AA included: L-tryptophan (Trp), L-arginine (Arg), L-cysteine (Cys), L-methionine (Met), L-alanine (Ala), L-phenylalanine (Phe), L-lysine (Lys), L-valine (Val), L-glycine (Gly), and L-leucine (Leu). The wild mushrooms: Lactarius piperatus, Amanita caesarea, Lactarius deliciosus, Lycoperdon pyriforme, Macrolepiota procera, and cultivated mushrooms: Agaricus bisporus, Boletus aestivalis, Cantharellus cibarius, Pleurotus ostreatus, and Agaricus bisporus var. avellaneus were investigated in this study. The AA was determined by HPTLC method and quantified with a Camag TLC scanner and WINCAT software by scanning the plates at 540 nm. The TPC was spectrophotometrically estimated as gallic acid equivalents/g of fresh weight according to Folin-Ciocalteu’s method. The radical scavenging activity (RSA) of mushroom extracts was determined by DPPH assay. The highest content of Ala, Gly, Phe, Lys, Val, and Leu was found in Pleurotus ostreatus. The total phenolic content (mg GAE/g) in investigated mushrooms ranged from 1.90 to 35.56, and the % RSA ranged from 43.88 to 90.17. This study promotes the consumption of food rich in bioactive compounds, mushrooms being among such food. Further research on mushrooms from Bosnia and Herzegovina and their benefits in the overall maintenance of human health and protection from age-related diseases is necessary.